2023
DOI: 10.1177/03635465231188114
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Osteoarthritis at Long-term Follow-up in Patients Treated for Symptomatic Femoroacetabular Impingement With Hip Arthroscopy Compared With Nonsurgically Treated Patients

Abstract: Background: Femoroacetabular impingement (FAI) is a common cause of hip pain, especially in young patients. When left untreated, it has been demonstrated to be a risk factor for the onset or progression of osteoarthritis (OA) and has been identified as one of the main contributors leading to the need for total hip arthroplasty (THA) at a young age. While the short-term therapeutic potential of hip arthroscopy is widely recognized, little is known regarding its potential mid- to long-term preventive effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Nepple et al 14 demonstrated that in a group of 23 hips that underwent femoroplasty versus 17 that did not, at the 16-year follow-up 78% of those that received bony correction went on to THA-free survivorship compared with the 41% that did not. Husen et al 8 unequally compared 132 symptomatic hips that underwent arthroscopy with 982 asymptomatic hips at a mean follow-up of 12.5 years and found that 12% of the operative hips progressed to To ¨nnis grade 2 compared with 22% of the nonoperative hips. Not only did this study fail to use the asymptomatic contralateral hip as an individual control for nonoperative hips, but also femoroplasty was only performed 93% of the time, labral repair was performed 91% of the time, and capsular repair was performed 45% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Nepple et al 14 demonstrated that in a group of 23 hips that underwent femoroplasty versus 17 that did not, at the 16-year follow-up 78% of those that received bony correction went on to THA-free survivorship compared with the 41% that did not. Husen et al 8 unequally compared 132 symptomatic hips that underwent arthroscopy with 982 asymptomatic hips at a mean follow-up of 12.5 years and found that 12% of the operative hips progressed to To ¨nnis grade 2 compared with 22% of the nonoperative hips. Not only did this study fail to use the asymptomatic contralateral hip as an individual control for nonoperative hips, but also femoroplasty was only performed 93% of the time, labral repair was performed 91% of the time, and capsular repair was performed 45% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Structural disorders of the hip, such as femoroacetabular impingement syndrome (FAIS) and hip dysplasia, are associated with abnormal intra-articular loading of the hip joint, which can result in pain, decreased hip function, and increased risk of osteoarthritis (Husen et al, 2023; Song et al, 2019). Understanding the relationship between movement strategies, muscle forces, and hip contact forces (HCFs) can provide insight into the mechanisms underlying the etiology and treatment effectiveness of structural hip disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Two decades after Dr. Ganz's publication, hip arthroscopy studies with 10 or more years of follow-up are appearing with increasing frequency. 2,3,5,9,15,16 In this month's American Journal of Sports Medicine (AJSM), Lamba and colleagues 12 share with us their institution's early experience in the realm of hip arthroscopy. They report the results of the arthroscopic debridement of acetabular labral tears from 1996 to 2010 with a minimum 13-year follow-up.…”
mentioning
confidence: 99%
“…Two decades after Dr. Ganz's publication, hip arthroscopy studies with 10 or more years of follow-up are appearing with increasing frequency. 2,3,5,9,15,16…”
mentioning
confidence: 99%